ANALISIS PUTUSAN HAKIM TERHADAP DAKWAAN BEBAS DALAM KASUS NARKOTIKA STUDI (NOMOR: 667/PID.SUS/2018/PN JMB) DALAM PERSPEKTIF HUKUM PIDANA DAN HUKUM PIDANA ISLAM - Siti Aina; Ruslan Abdul Ghani; Robi’atul Adawiyah (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Analysis of the judge's decision on the acquittal of the defendant who was charged by the public prosecutor with Article 114 paragraph 1 of Law no. 35 of 2009 with a sentence of 17 years in prison, but the judge gave an acquittal on the grounds that the defendant's urine test was negative, this is what made the author interested in re-analyzing the judge's decision given, because according to the author if as a user it cannot be proven then the defendant can be charged with the article as a dealer, which we all know that the law for dealers is greater than for users, and here the author not only analyzes it from a criminal law perspective but also from an Islamic criminal law perspective. The purpose of this study is to find strong reasons that are the basis for the judge's consideration in giving an acquittal to the defendant based on criminal law and Islamic criminal law. Because in the defendant's charges there are several pieces of evidence attached to the letter of indictment against the defendant. In this Thesis research, the author uses a Qualitative research method using content analysis by describing the content that the author gets and the research approach uses a normative legal method. This means that this method is used because the data used is in the form of Literature, namely Library research. by reading and citing writings that are related to the problems discussed in the form of books, articles, manuscripts and other documents related to the problems discussed. The results of the study explain comparatively analyzing the judge's decision against the defendant who gave an acquittal based on criminal law and Islamic criminal law and analyzing whether the judge's decision has fulfilled the sense of justice for all parties involved.